Black and Asian Theatre in Britain - Chambers, Colin (Taylor & Francis, 2011)
Black and Asian Theatre in Britain is an unprecedented study tracing the history of 'the Other' through the ages in British theatre. The diverse and often contradictory aspects of this history are expertly drawn together to provide a detailed background to the work of African, Asian, and Caribbean diasporic companies and practitioners. Colin Chambers examines early forms of blackface and other representations in the sixteenth century, through to the emergence of black and Asian actors, companies, and theatre groups in their own right. Thorough analysis uncovers how they led to a flourishing of black and Asian voices in theatre at the turn of the twenty-first century. Figures and companies studied include: Ira Aldridge Henry Francis Downing Paul Robeson Errol John Mustapha Matura Dark and Light Theatre The Keskidee Centre Indian Art and Dramatic Society Temba Edric and Pearl Connor Tara Arts Yvonne Brewster Tamasha Talawa. Black and Asian Theatre in Britain is an enlightening and immensely readable resource and represents a major new study of theatre history and British history as a whole.